DIGITAL PROSPECTIVE OF HERMENEUTICS IN MODERN LITERARY STUDIES - ABDUGANIEVA, Jamilya Rustamovna (The Lingua Spectrum, 2025)
This extended article offers an expanded scholarly investigation of hermeneutics within modern literary studies, emphasizing its transformation under the influence of digital methodologies and the broader epistemological shifts characteristic of twenty‑first‑century philology. It examines the theoretical evolution of hermeneutics from its classical philosophical origins to its integration into contemporary digital humanities, focusing on how modern interpretive practices reshape the author–text–reader triad, the multiplicity of meaning, and the hermeneutic act itself. The work highlights the methodological continuities and ruptures that define current hermeneutic inquiry and argues for a hybrid model capable of reconciling humanistic reflection with computational approaches.